Research on magnetic bead motion characteristics based on magnetic beads preset technology - Zhao Li (Nature Portfolio, 2021)
Abstract In order to improve the detection efficiency and accuracy of microfluidic chip, a magnetic beads preset technology were designed by using double permanent magnets as external magnetic field and the motion characteristics of preset magnetic beads were studied. The control principle of magnetic beads preset technology was introduced in detail, and the control structure was designed. The coupled field characteristics for magnetic beads in microchannels were analyzed, and the motion models of magnetic beads were established based on the magnetic beads preset technology, including capture motion and mixing motion. The relationship between the magnetic field force and the flow velocity for capturing magnetic bead, and the mixing time under the influence of flow field and magnetic field were derived. The magnetic beads preset technology effect was verified by experiments and numerical simulations were developed to analyze the influence of aspect ratio of permanent magnet on magnetic field. The study showed that the accuracy and efficiency of the magnetic bead control in the microchannel could be better realized by the magnetic beads preset technology. The derivation of the magnetic bead motion model can understand the motion characteristics of the magnetic bead more clearly, facilitate accurate control of the magnetic bead, and improve the success rate of the microfluidic detection.